Sensoriamento remoto na gestão da agricultura irrigada por pivô central e cobertura do solo com gramíneas tropicais no estado do Espírito Santo - Goncalves, Morgana Scaramussa (2020)
Agriculture is an important sector in the economy of the State of Espírito Santo, responsible for 9.3% of the State's GDP. However, the productivity of the Capixaba herd is still very low, as it is almost exclusively pasture, and these are largely degrade